THE EFFECT OF SERVICE QUALITY ON DONOR SATISFACTION IN BLOOD TRANSFUSION UNIT DR SOEKARDJO HOSPITAL, TASIKMALAYA - Devi Pahyastrivi; Etih Henriyani (JGSRD: Journal of Government Science and Rural Development, 2022)
Research in the background i there are complaints of donor dissatisfaction with the quality of service so that it has an impact on the uncertainty of the number of donors and the stock of blood transfusions every month. The purpose of the study was to determine the level of service quality, donor satisfaction, to determine the effect of service quality on blood donor satisfaction at U TDRS dr Soekardjo Tasikmalaya City. Quantitative method with a sample of 86 respondents. Collecting data by observation, interviews and questionnaires. T eknik data analysis by statistical test research instruments, the level of service quality and donor satisfaction, the correlation of the two variables, hypotheses, to calculate the magnitude of the effect of service quality on donor satisfaction. The results of the study on service quality in good categories based on core service dimensions with an average of 239, human element of service with an average of 341.5, Systematization of service delivery with an average of 383, tangibles of service with an average of 359.5 and social responsibility with an average of 407. Donor satisfaction is in good category based on the dimensions of core service with an average of 2324, human element of service with an average of 350.5, systematization of service delivery with an average of 382.5, tangibles of service with an average of 360 and social responsibility with an average of 408.5. The result of product moment correlation is 0.98, the effect of service quality on donor satisfaction with the coefficient of determination is 96%. U ji hypothesis with a confidence level of 95% at α = 0.05 and N = 86, obtained t table = 1.98793 and t = 44.884, then the hypothesis Ho is rejected and Ha accepted .